Human Capital and the Economic Convergence Mechanism: Evidence from China - Xiaobei Zhang; Haizheng Li; Xiaojun Wang; Belton M. Fleisher (Institute of Labor Economics (IZA), 2019)
We examine the mechanism by which human capital affects economic growth and convergence, using provincial level panel data from China. We specify alternative measures of human capital and apply them to an enhanced growth model which we estimate parametrically, nonparametrically, and with a threshold model. Our results show that economic convergence is pronouncedly conditional on human capital across all our measures of human capital. The positive "benefit of being backward" due to lower initial income is almost trumped by the negative impact of low levels of human capital among the poorest areas.
Keywords: R11; O47; C33; 330; human capital; economic convergence; regional economic development